Intraductal Oncocytic Papillary Neoplasm of the Pancreas: A Radio-Pathological Case Study - Fischer, Michael A; Donati, Olivio; Heinrich, Stefan; Weber, Achim; Hany, Thomas F; Soldini, Davide; Alkadhi, Hatem; Marincek, Borut; Scheffel, Hans (JOP. Journal of the Pancreas, 2016)
Context An intraductal oncocytic papillary neoplasm is a rare pancreatic tumor with the potential of developing invasive carcinoma. Its differentiation from other cystic-like neoplasms of the pancreas, such as intraductal papillary mucinous neoplasms, is a challenge for pancreatic imaging. Case report We present the case of a 76-year-old male with painless jaundice caused by an intraductal oncocytic papillary neoplasm of the pancreas. The imaging findings on computed tomography, magnetic resonance including diffusion-weighted imaging, and 18F-fluorodeoxyglucose positron emission tomography are presented and the radio-pathological correlations are discussed. Conclusion An intraductal oncocytic papillary neoplasm of the pancreas appears as a cystic tumor communicating with the dilated pancreatic duct featuring intraductal tumor nodules. Intraductal oncocytic papillary neoplasms show a high 18F-fluorodeoxyglucose-uptake in positron emission tomography and low diffusion values in diffusion-weighted imaging including apparent diffusion coefficient maps which may be a valuable attribute in distinguishing these rare lesions from intraductal papillary mucinous neoplasms. Image: Original attenuation-corrected coronal PET image.